Impact of auditory stimulation nursing protocol on auditory response in cerebrovascular stroke patients - Mohammed ElSayed Zaky; Hanan Ahmed Al Sebaee; Nagat El Morsy Ibrahiem; Heba Ahmed Mohammed; Mohammad Edrees Mohammad (Wolters Kluwer Medknow Publications, 2024)
Objectives: The objective of the study was to explore the impact of auditory stimulation protocol on auditory response in cerebrovascular stroke (CVS) patients. Materials and Methods: A pre-posttest nonequivalent control group quasi-experimental study was conducted at Al Mainal Hospital at Al Kars Einy Hospital, Cairo University, among 60 CVS patients, and the sample was randomly assigned through a coin to allocate subjects to study or control group (30 for each group). Auditory stimulation techniques were applied three times per week for the study group for two consecutive weeks. Patients in the control group received only routine hospital care during the study period. The Glasgow Coma Scale (GCS) score for assessing the neurological function and level of arousal and the auditory subscale score of Western Neuro Sensory Stimulation Profile (WNSSP) for assessing auditory response were recorded and compared between the two groups before and after the intervention. Results: There were statistically significant differences between the study group and the control group regarding third reading of GCS score (11.5 ± 0.3 vs. 10.6 ± 0.9, t = 4.676, P = 0.000). The scores of all auditory subscales of WNSSP in the study groups increased after implementing the auditory stimulation protocol (P < 0.05). Conclusion: Utilizing the auditory stimulation protocol by nurse proves to be an effective method for enhancing hearing responses in individuals with CVS.